Rumah Datuk Alang Mat Latif, Lot 123, Kampong Bandar Tua, Mukim Pasir Salak, Kampong Gajah, Perak / [lukisan teknik] - Rusli Hj Nor; Ishamuddin Abd Majid; Mazani Harun; Norhayati Abu Bakar; Salleha Abdul Kadir (KL : UTM, 1986)
Kajian lukisan terukur (Jabatan Senibina) -- Universiti Teknologi Malaysia, 1986